Determinação de fósforo por espectrometria de emissão ótica com plasma indutivamente acoplado em matrizes contendo metais alcalinos e alcalinos terrosos - Santos, Francisco Furtado dos (2008)
The Phosphorus is an essential element for in body human required by cells for the operation; is the largest constituent of the bones of the human body in the form of calcium phosphate. The determination of phosphorus can be using different techniques is like Molecular Absorption Spectrophotometry, Ion Chromatography, Phosphorescence, Atomic Emission spectrometry, among others. This work has a goal to develop a methodology for determination of phosphorus in digest of organic samples by optical emission spectrometry with plasma inductive coupled. The methodology developed studies 4 lines of emission of this element and two instrumental settings, axial and radial. Only a wavelength 213.617 and 214.914nm had sensitivity suitable for the study. The linear range investigated was 50 to 300 mg. L-1. The investigation of the interference effect was studied by alkali metals (Na and K) and alkali earth (Ca and Mg) in the sign of phosphorus. The positive interference was obtained for all metals investigated with increase in the signal in up to 50% for potassium with interference. To resolve this effect interfering was investigated the increased power of radiation from the plasma generated and use of internal standard. The use of internal standard has been more appropriate, in case the Sc, with corrections of 90% reduction of interference. The methodology developed was evaluated in interlaboratory certified samples and the results were compatible with errors less than 10%. The content of phosphorus was determined in samples of banana subjected to a treatment of fertilization, and the values obtained in the order of 765 and 1.167mg.L-1